1986
DOI: 10.1103/physrevlett.57.1753
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Supercooling of Liquids in Porous Glass

Abstract: The supercooling and freezing of a restricted liquid has been studied by the probing of its molecular dynamics with picosecond optical techniques. A newly developed transparent porous host material makes it possible to study the liquid viscosity as a function of the confining pore radius and temperature. The observed behavior is remarkably different from that of an ordinary liquid, and can be interpreted in terms of a simple model. PACS numbers: 64.70.Dv, 61.25.Em, 62.10.+$, It is well known that the propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
136
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(140 citation statements)
references
References 10 publications
4
136
0
Order By: Relevance
“…The pore size in zeolites (between 0.2 and 1 nm) is close to the sizes of small molecules like CH 4 or CO 2 , and can be tuned by ion exchange in the zeolite matrix. Because of this similarity in size, it is no surprise that the diffusion coefficient of methane can vary by as much as 6-10 orders of magnitude, depending on the pore topology.…”
Section: Transport In Nanochannelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pore size in zeolites (between 0.2 and 1 nm) is close to the sizes of small molecules like CH 4 or CO 2 , and can be tuned by ion exchange in the zeolite matrix. Because of this similarity in size, it is no surprise that the diffusion coefficient of methane can vary by as much as 6-10 orders of magnitude, depending on the pore topology.…”
Section: Transport In Nanochannelsmentioning
confidence: 99%
“…As an example of phase transition shifts in confinement, in work in which time-resolved optical experiments were used to study the dynamics of liquid oxygen in pores with diameters of between 2.2 and 18.7 nm [4], it was experimentally found that a supercooling of almost 20% below the bulk freezing point is obtained in the smallest pores. The freezing-point depression follows the relationship:…”
Section: Phase Equilibria In Nanochannelsmentioning
confidence: 99%
“…13,14 According to a study combining Dielectric Relaxation Spectroscopy and Differential Scanning Calorimetry experiments with Grand Canonical Monte Carlo simulations, 15 uids conned in cylindrical nanopores (e.g. MCM41) should freeze into a single crystalline structure for average pore diameters larger than 20s (s being the diameter of the guest molecule).…”
Section: 12mentioning
confidence: 99%
“…The 1 H spectra, on the other hand, showed that there is always a certain amount of water molecules present inside the porous network, which it is difficult to completely remove. Finally, the 13 C spectra showed evidence of isotropic rotational diffusion of the solvated SNP complexes inside the matrix pores. Therefore, the H 2 O present in the pores could not be reasonably modelled by the PDF analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation